Discrimination and social justice in education: Diversity narratives in Portuguese schools - Mateus, S. (7th Global Meeting on Law & Society - Rage, Reckoning, & Remedy, 2022)
Discrimination on the basis of race and ethnic origin assume a central role in studies on education and children of immigrants, since it is strong obstacle to integration and affects schooling processes. The experience of discrimination at school uncovers important limits to social justice in education. Teachers and other school actors not only have specific perceptions of social justice, but also contribute to its production and dissemination in the school environment. How can they counteract relations of subordination and discrimination and deliberately and consciously contextualise their educational practice within prevailing patterns of social injustice? In this presentation we intend to discuss this issue by reflecting on the narratives about of ethnic and racial diversity in the school environment.